2009
DOI: 10.1111/j.1365-2893.2008.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of non‐invasive markers and FibroScan values during HCV treatment

Abstract: The recent advent of non-invasive methods for assessment of fibrosis allows serial assessments in all patients with hepatitis C. The aim of this prospective study was to evaluate changes in liver fibrosis, as measured with non-invasive methods, in a large cohort of HCV-infected patients with and without treatment. From May 2003 through March 2006, all previously untreated HCV-infected patients were enrolled in this study. Liver fibrosis was staged with FibroScan and Fibrotest at inclusion, then every year in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 35 publications
(52 reference statements)
2
73
3
1
Order By: Relevance
“…Previously it has been shown that noninvasive tests should be repeated to monitor patients and predict their outcome [21]. It was evidenced before the DAA era, that treatment was the only factor independently associated with a fall in the TE values [22]. There are more recent studies [23,24] showing significant reduction of the liver stiffness values and also the other validated fibrosis scores (APRI, FIB4) at SVR as well as portal hypertension, similar to our study.…”
Section: Discussionsupporting
confidence: 87%
“…Previously it has been shown that noninvasive tests should be repeated to monitor patients and predict their outcome [21]. It was evidenced before the DAA era, that treatment was the only factor independently associated with a fall in the TE values [22]. There are more recent studies [23,24] showing significant reduction of the liver stiffness values and also the other validated fibrosis scores (APRI, FIB4) at SVR as well as portal hypertension, similar to our study.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, TE could be useful for evaluating fibrosis regression in patients with chronic hepatitis C achieving sustained viral eradication [92][93][94] or for monitoring fibrosis progression in untreated patients.…”
Section: Monitoring Of Disease Progressionmentioning
confidence: 99%
“…However, because of sampling error, liver biopsy can overestimate or underestimate the degree of liver fibrosis. Increasingly, some physicians are commencing therapy in individuals without performing liver biopsy [29]. Liver biopsy is an important diagnostic tool in the work-up of patients with liver disease.…”
Section: Investigations For Liver Diseasementioning
confidence: 99%